2023
DOI: 10.1186/s40658-023-00587-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of various penalty parameter values in Q.Clear algorithm for rectal cancer detection on 18F-FDG images using a BGO-based PET/CT scanner: a phantom and clinical study

Fatemeh Sadeghi,
Peyman Sheikhzadeh,
Saeed Farzanehfar
et al.

Abstract: Background The Q.Clear algorithm is a fully convergent iterative image reconstruction technique. We hypothesize that different PET/CT scanners with distinct crystal properties will require different optimal settings for the Q.Clear algorithm. Many studies have investigated the improvement of the Q.Clear reconstruction algorithm on PET/CT scanner with LYSO crystals and SiPM detectors. We propose an optimum penalization factor (β) for the detection of rectal cancer and its metastases using a BGO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…This optimization will additionally depend on the purpose of scan, the tissue(s) of interest, the injected dosage, and/or the lesion size. A study including both phantom and clinical assessment of a BPL reconstruction algorithm using F-18 FDG PET/CT by Sadeghi et al revealed that lesion size impacts the optimal b value when examining patient images [39]; this mirrors our results showing the strong dependence of sphere size on SNR, CNR, SUV max , and RC with Cu-64. It will be essential to fully assess BPL on clinical images prior to usage for patient diagnosis in routine PET/CT imaging.…”
Section: B >supporting
confidence: 85%
“…This optimization will additionally depend on the purpose of scan, the tissue(s) of interest, the injected dosage, and/or the lesion size. A study including both phantom and clinical assessment of a BPL reconstruction algorithm using F-18 FDG PET/CT by Sadeghi et al revealed that lesion size impacts the optimal b value when examining patient images [39]; this mirrors our results showing the strong dependence of sphere size on SNR, CNR, SUV max , and RC with Cu-64. It will be essential to fully assess BPL on clinical images prior to usage for patient diagnosis in routine PET/CT imaging.…”
Section: B >supporting
confidence: 85%